Analysis of Pesticide Thiametoxam Pesticide Residu Cabbage in Vegetables (Brassica oleracea var. Capitata L) - Muslim, Yuli Pratiwi (UNIVERSITAS SAM RATULANGI, 2015)
Analysis of Pesticide Thiametoxam Pesticide Residu Cabbage in Vegetables (Brassica oleracea var. Capitata L) Yuli Pratiwi Muslim1), Fatimawali1), WidyaAstuty Lolo1) 1)Program Studi Farmasi, FMIPA UNSRAT, MANADO ABSTRACT Thiamethoxam is a dangerous chemical and toxic that added to vegetables for kill all kinds of insects and pests. The purposes of this study were to identify pesticide residues of tiamethoxam in vegetables cabbage and determine the levels of thiamethoxam pesticide residues which contained in cabbage. Sampling locations were Bahu market, Karombasan market, Bersehati market and Rurukan village. Thiamethoxam pesticide residue level was identified and determined using High Performance Liquid Chromatography HPLC. HPLC parameters which used in analysis were mobile phase of methanol-water (60:40 v/v), flow rate 1 mL/min, temperature 33ºC and wavelength of 253 nm. The result shows that sample of Rurukan village and Karombasan market contains residue pesticide of thiamethoxam by 5.66 mL/minutes. Key words :Thiamethoxam, cabbage and HPLC, Manado ABSTRAK Tiametoksam adalah senyawa kimia berbahaya dan beracun yang biasa digunakan pada sayuran untuk mematikan segala jenis serangga dan hama. Tujuan penelitian yaitu untuk mengidentifikasi residu pestisida pada sayur kubis dan menentukan kadar residu pestisida tiametoksan yang terkandung dalam sayur kubis. Lokasi pengambilan sampel sayur kubis ialah pasar Bahu, pasar Karombasan, pasar Bersehati dan desa Rurukan. Residu pestisida tiametoksam diidentifikasi dan ditetapkan kadar menggunakan Kromatografi Cair Kinerja Tinggi KCKT. Parameter HPLC yang digunakan yaitu fasa gerak air : metanol (60:40 v/v), lajualir 1 mL/menit dengan suhu 33ºC dan panjang gelombang 253 nm. Hasil penelitian menunjukan bahwa sampel dari desa rurukan dan pasar karombasan positif mengandung residu pestisida tiametoksam dengan kadar 5,66 mL/menit. Kata kunci: Tiametoksam, Kubis, KCKT, Manado